PENGARUH KOMISARIS INDEPENDEN, KEPEMILIKAN MANAJERIAL, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAA - Afridayani, Afridayani; Mardianti, Eva (Jurnal Ekonomi : Journal of Economic, 2024)
This study aims to determine the influence of independent commissioners, managerial ownership and institutional ownership on company value. The population in this research are companies listed on the Indonesia Stock Exchange (BEI) in the Infrastructure sector for the 2018-2022 period with a sample size of 75 with certain criteria. The sampling technique uses purposive sampling. Data analysis in this study used multiple linear regression analysis. The results of this research show that: 1) Independent Commissioners have no significant effect on Company Value. 2) Managerial ownership has no significant effect on company value. 3) Institutional Ownership has a significant effect on Company Value. 4) Independent Commissioners, Managerial Ownership, Institutional Ownership simultaneously influence Company Value.